A systematic revision of Tatia (Siluriformes: Auchenipteridae: Centromochlinae) - Luisa Maria Sarmento-Soares; Ronaldo Fernando Martins-Pinheiro (Neotropical Ichthyology)
The auchenipterid catfish genus Tatia is revised. Twelve species are recognized including three described as new. Tatia is diagnosed by the hyomandibula elongated anterodorsally, the anal-fin base of adult males reduced in length, and the caudal peduncle laterally compressed and deep with a middorsal keel. Tatia aulopygia occurs in the Madeira river drainage and is distinguished by the reduced cranial fontanel in adults and male modified anal fin with middle rays reduced in length. Tatia boemia, known from the upper Uruguay river drainage, is distinguished by its unique color pattern with dark chromatophores on the sides of body. Tatia brunnea from river basins in Suriname and French Guiana and the Negro river drainage, Amazon basin, is recognized by its wide head and mouth and by the male modified anal fin with sharply pointed tip. Tatia dunni, from the upper Amazon basin, is recognized by its narrow head, long postcleithral process in some specimens, and body coloration with irregular blotches or stripes. Tatia galaxias, endemic to the Orinoco river basin, is distinguished by its large eye and short snout. Tatia gyrina, distributed in the upper and central Amazon basin and in northern Suriname, has a uniquely reduced mesethmoid, slightly protruding lower jaw, second nuchal plate with slightly concave lateral borders, third nuchal plate reduced, small prevomer, low number of ribs, low number of vertebrae and sexual dimorphism regarding intumescent male genital papilla. Tatia intermedia, recorded from central and lower Amazon basin, Tocantins river, and coastal drainages in Guyana, Suriname, French Guiana, and eastern Pará State, Brazil, is distinguished by the short postcleithral process, small eye and long snout. Tatia neivai, from the upper Paraná river , Paraguay river and upper Paraíba do Sul river basin, is distinguished by its unique vertebral count and caudal-fin coloration consisting of transverse dark bars. Tatia strigata, from central Amazon basin and Negro river, is distinguished by its horizontally striped color pattern and the modified male anal fin with middle rays reduced in length. Tatia caxiuanensis, a new species described from the Curuá river, lower Amazon basin, is recognized by its wide cranial fontanel and distinctive anal fin in mature males. Tatia meesi, a new species described from the Essequibo river basin, Guyana, is distinguished from congeners by the cranial fontanel with two separate openings and thin nasal bone. Tatia nigra, a new species described from the central Amazon basin, is distinguished by its short postcleithral process, low number of vertebrae, and dark color pattern. All twelve species of Tatia are described or redescribed and a key to species is provided.